2015
DOI: 10.1586/17474124.2015.1038241
|View full text |Cite
|
Sign up to set email alerts
|

Symptom management in inflammatory bowel disease

Abstract: Patients with inflammatory bowel disease can present with a wide variety of symptoms. Most are related to disease activity and should be managed with appropriate medical therapy for inflammatory bowel disease. However, some patients may develop symptoms due to the side effects of the medications, or due to immunosuppression. In these cases, the offending medications should be discontinued until resolution of the symptoms and a few may be able to restart therapy. Symptoms can also occur as an extraintestinal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 167 publications
0
9
0
6
Order By: Relevance
“…These symptoms can be embarrassing, uncomfortable, and affect the quality of life. Therefore, it is important to develop therapeutic approaches to relieve the symptoms of UC (Abraham, 2015). Here, we showed that GAE and DMB treatment could ameliorate TNBS-induced rat model weight loose and food/water intake decrease, increase colon length, and attenuate DAI and histopathological score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These symptoms can be embarrassing, uncomfortable, and affect the quality of life. Therefore, it is important to develop therapeutic approaches to relieve the symptoms of UC (Abraham, 2015). Here, we showed that GAE and DMB treatment could ameliorate TNBS-induced rat model weight loose and food/water intake decrease, increase colon length, and attenuate DAI and histopathological score.…”
Section: Discussionmentioning
confidence: 99%
“…Medications targeting these receptors and their signaling pathways have been developed for UC symptom management. Alosetron (5-HT3 antagonist), Darifenacin (a selective muscarinic M3 receptor inhibitor), and ebastine (a selective H1 receptor inhibitor) have been used to reduce the colonic contractile response and abdominal pain in UC (Bharucha et al, 2010; Abraham, 2015). However, combination of medications causes inconvenience and increases the possibility of noncompliance.…”
Section: Discussionmentioning
confidence: 99%
“…Crohn hastalığı en sık olarak distal ince barsak ve kolonu tutmasına karşın, ağızdan anüse kadar gastrointestinal kanalın herhangi bir yerinde segmenter tarzda görülebilir. Ülseratif kolitteki inflamasyon ise genellikle kolon ile sınırlı olmakla birlikte arada sağlam segment bırakmaksızın diffüz yüzeyel tutulum göstermektedir [1][2][3][4] . Ülseratif kolit ve CH çok çeşitli semptomlar ile ortaya çıkabilmektedir.…”
unclassified
“…UC is an idiopathic disease characterised by recurrent episodes of inflammation that predominantly affects the mucous and submucosal layers of the colon, causing gastrointestinal lesions, including ulcers and open wounds on the surface of the lining, diarrhoea and haemorrhage ( 16 , 17 ) . The clinical course is characterised by periods of remission and exacerbation, which may occur spontaneously or in response to treatment ( 18 ) .…”
mentioning
confidence: 99%